The Function and Social Value of Death Rituals: A Comparative Study of Confucian and Muslim Traditions - Putra, Aqiel Sifa' Abdallah (Al-Adyan: Journal of Religious Studies, 2024)
The purpose of this research is to uncover the similarities and differences between the Ceng Beng and Grave Pilgrimage rituals and their impact on societal dynamics. Additionally, it highlights how these rituals create sacred and profane spaces for the community. Equally important, the study examines the social functions and values inherent in these rituals.The qualitative research method is used to collect data in the literature review with a descriptive analysis and comparative approach. Then it is analyzed using Durkheim's life cycle ritual theory. This article demonstrates that although the two death rituals have similarities and differences, they provide an understanding of the sacred and profane aspects within the ritual life cycle. Beyond their sacred aspects, the profane elements of these rituals play a significant role in the social functions and values of society, such as affection, family harmonization, reminders of mortality, filial piety, solidarity, and tolerance. The Ceng Beng and Ziarah Kubur rituals indicate that they are not only religious obligations but also social obligations within community life.Tujuan penelitian ini adalah untuk mengungkap persamaan dan perbedaan antara ritual Ceng Beng dan Ziarah Kubur, serta dampaknya pada dinamika masyarakat. Selain itu juga menyoroti bagaimana kedua ritual tersebut menciptakan ruang sakral dan profan bagi masyarakat. Tidak kalah penting fungsi sosial dan nilai-nilai dalam ritual tersebut juga tidak luput dalam kajian ini. Metode penelitian kualitatif menjadi pegangan dalam mengambil data-data dalam studi pustaka dengan pendekatan deskriptif analisis dan komparatif. Kemudian dianalisis menggunakan teori ritual life cycle oleh Durkheim. Artikel ini menunjukkan bahwa kedua ritual kematian, meskipun memiliki persamaan dan perbedaan, memberikan pemahaman tentang aspek sakral dan profan dalam siklus kehidupan ritual. Selain aspek sakral, aspek profan dari ritual-ritual ini memainkan peran penting dalam fungsi sosial dan nilai-nilai masyarakat, seperti kasih sayang, harmonisasi keluarga, pengingat kematian, bakti kepada orang tua, solidaritas, dan toleransi. Ritual Ceng Beng dan Ziarah Kubur menunjukkan bahwa keduanya tidak hanya merupakan kewajiban agama, tetapi juga kewajiban sosial dalam kehidupan bermasyarakat.